2020
DOI: 10.1111/joor.12971
|View full text |Cite
|
Sign up to set email alerts
|

Is there association between dental malocclusion and bruxism? A systematic review and meta‐analysis

Abstract: Objectives Given that current literature largely dissociates dental malocclusion and bruxism, the objective of this study was to gather, through a systematic review, scientific evidence to support their relationship. Methodology This study was performed according to the PECO strategy (where P = general population; E = dental malocclusion; C = no dental malocclusion; and O = bruxism). Literature searches were conducted without language or date restrictions in the following databases: PubMed, Scopus, the Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The relationship between bruxism and occlusion has not been well understood although it has been investigated in dentistry [ 23 ]. Although some dentists have suggested that malocclusion may be the etiologic factor of bruxism, a recent review concluded that there is no evidence to support that belief [ 14 ]. However, bruxism may be a risk factor of malocclusion [ 7 , 9 , 13 , 14 ] because the wearing of dental tissues increases since bruxism generates higher forces due to the increased activity of the masticatory muscles, and the contacts between antagonist teeth get larger and flatter than they do in a normal occlusal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between bruxism and occlusion has not been well understood although it has been investigated in dentistry [ 23 ]. Although some dentists have suggested that malocclusion may be the etiologic factor of bruxism, a recent review concluded that there is no evidence to support that belief [ 14 ]. However, bruxism may be a risk factor of malocclusion [ 7 , 9 , 13 , 14 ] because the wearing of dental tissues increases since bruxism generates higher forces due to the increased activity of the masticatory muscles, and the contacts between antagonist teeth get larger and flatter than they do in a normal occlusal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although some dentists have suggested that malocclusion may be the etiologic factor of bruxism, a recent review concluded that there is no evidence to support that belief [ 14 ]. However, bruxism may be a risk factor of malocclusion [ 7 , 9 , 13 , 14 ] because the wearing of dental tissues increases since bruxism generates higher forces due to the increased activity of the masticatory muscles, and the contacts between antagonist teeth get larger and flatter than they do in a normal occlusal relationship. This situation allows the horizontal movement of the mandible against the maxilla, which increases stimulation of the alveolar bone [ 13 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another systematic review and meta-analysis set out to gather scientific evidence to support the relationship between dental malocclusion and bruxism. 411 The study was guided by the PECO strategy (P=general population; E=dental malocclusion; C=no dental malocclusion; O=bruxism). Literature searches were performed without language or date restrictions in the following databases: PubMed, Scopus, the Web of Science, the Cochrane Library, LILACS/BBO through VHL, and the gray literature.…”
Section: Sleep Bruxism and Temporomandibular Disorders (Tmds)mentioning
confidence: 99%